MENINGKATKAN KREATIVITAS ANAK USIA 5-6 TAHUN MELALUI KEGIATAN MEMBATIK ECOPRINT - Fitriah; Kaspul Anwar; Raoda Tul Jannah Maruddani; Amiroh; Jasna Febriani (Irfani, 2025)
This study aims to enhance the creativity of 5-6 year-old children at Taman Kanak-Kanak Islam Ahsan in Jambi City through ecoprint batik activities using the Classroom Action Research (CAR) method. Based on observations conducted by the researcher from December 18-20, 2023, involving 16 children at TK Islam Ahsan, daily and weekly analyses indicated that 12 children had not shown adequate development in their creativity. Specifically, 75% of the children were categorized as "Not Developing" (BB) in terms of curiosity and challenge progress in the art creativity indicators. The research employed the CAR method, which consisted of two cycles. In Cycle I, the intervention involved ecoprint batik activities using natural materials such as oranges and celery. In Cycle II, evaluation and reflection on the results from the previous cycle were carried out. Observations revealed a significant improvement in drawing skills and the creation of works resembling real forms. In both Cycles I and II, there was a shift to the "Starting to Develop" (MB), "Developing as Expected" (BSH), and "Developing Very Well" (BSB) categories. Supporting factors in this study included the engaging and enjoyable ecoprint method, skilled educator support, and a positive learning environment. Conversely, limiting factors included time constraints, resource availability, and individual differences in children's skills and interests